Popular Violence and Popular Heresy in Western Europe, c1000-1179 - Moore, Robert I. (Studies in church history, 1984)
In general modern writers on popular heresy in the high middle ages have shared the opinion of contemporary observers that the capacity of dissident preachers to attract a popular following, stimulate sentiments of intense devotion and loyalty, and canalise resentment of clerical exaction and abuse, constituted a significant threat to the authority of the Church. Hence, more or less explicitly, the extension of the theory and practice of coercion in the twelfth and thirteenth centuries has been seen as a defensive reaction designed (with the emphasis according to the preference of the historian) to protect clerical privilege and spiritual authority. There are, however, distinguished exceptions. In one of the few passages in his writings where religious persecution is discussed, Southern accounts for it thus: … those who bore authority in the church were agents with very limited powers of initiative. They were not free agents. Doubtless they were responsible for some terrible acts of violence and cruelty, among which the Albigensian Crusade holds a particular horror. But on the whole the holders of ecclesiastical authority were less prone to violence, even against unbelievers, than the people whom they ruled.